Konsep Manajemen Strategi Pemasaran Asuransi - Nuri Aslami; Ella Safitri (Transformasi Manageria: Journal of Islamic Education Management, 2022)
Insurance is a field of insurance business that has received great attention among the people of Indonesia. As an alternative insurance business, sharia insurance is relatively new compared to the conventional insurance business. The novelty of the sharia insurance business is the operation of its business activities based on principles. Considering the number of new companies (start-ups) that have sprung up which will definitely increase the competition in market share. Marketing strategies and competitive strategies are certainly needed by insurance companies to find out and improve the advantages of their products in order to compete in the midst of incessant global competition. Keywords: Strategy, Marketing, Insurance